Trends and Disparities in Cervical Spine Fusion Procedures Utilization in the New York State. Issue 10 (15th May 2018) - Feng, Rui; Finkelstein, Mark; Bilal, Khawaja; Oermann, Eric K.; Palese, Michael; Caridi, John
Abstract : Study Design: A retrospective review of the Statewide Planning and Research Cooperative System database of the New York State. Objective: This study examined the rate of increase of cervical spine fusion procedures at low-, medium-, and high-volume hospitals, and analyzed racial and socioeconomic characteristics of the patient population treated at these three volume categories. Summary of Background Data: There has been a steady increase in spinal fusion procedures performed each year in the United States, especially cervical and lumbar fusion. Our study aims to analyze the rate of increase at low-, medium-, and high-volume hospitals, and socioeconomic characteristics of the patient populations at these three volume categories. Methods: The New York State, Statewide Planning and Research Cooperative System (SPARCS) database was searched from 2005 to 2014 for the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) Procedure Codes 81.01 (Fusion, atlas-axis), 81.02 (Fusion, anterior column, other cervical, anterior technique), and 81.03 (Fusion, posterior column, other cervical, posterior technique). Patients' primary diagnosis (ICD-9-CM), age, race/ethnicity, primary payment method, severity of illness, length of stay, hospital of operation were included. All 122 hospitals were categorized into high-, medium-, and low-volume. Trends in annual number of cervical spine fusion surgeries in each of the three hospital volume groups were reported using descriptive statistics. Results: Low-volumes centers were more likely to be rural and non-teaching hospitals. African American patients comprised a greater portion of patients at low-volume hospitals, 15.1% versus 11.6% compared with high-volume hospitals. Medicaid and self-pay patients were also overrepresented at low-volume centers, 6.7% and 3.9% versus 2.6% and 1.7%, respectively. Compared with Caucasian patients, African American patients had higher rates of postoperative infection ( P  = 0.0020) and postoperative bleeding ( P  = 0.0044). Compared with privately insured patients, Medicaid patients had a higher rate of postoperative bleeding ( P  = 0.0266) and in-hospital mortality ( P  = 0.0031). Conclusion: Our results showed significant differences in hospital characteristics, racial distribution, and primary payments methods between the low- and high-volume categories. African American and Medicaid patients had higher rates of postoperative bleeding, despite similar rates between the three volume categories. This suggests racial and socioeconomic disparities remains problematic for disadvantaged populations, some of which may be attributed to accessibility to care at high-volume centers. Level of Evidence: 3